BIOLOGICAL ASPECTS OF RHAGOLETIS TOMATIS FOOTE (DIPTERA: TEPHRITIDAE) IN CHILEAN POPULATIONS OF II REGION (Acta Entomológica Chilena, 2022)
Observations both at the laboratory and in the field prove that probably Rhagoletis tomatis has at leastfive to six generations per year. This species present a low pupal diapause. Females deposite their eggsgregariously in unripen fruits. After ovipositing the females dragg the ovipositor in circle near ofpuncture and probably deposit a pheromone that is atractive for other females.